Diagnostic challenges and importance of early multidisciplinary intervention in acral melanoma: a case report (Dermatology Reports, 2025)
Acral melanoma (AM) is a rare subtype of melanoma that occurs on acral sites such as the palms, soles, and subungual regions. Due to its atypical presentation and frequent lack of pigmentation in the amelanotic variant (AAM), diagnosis is often delayed, leading to a poor prognosis. We present the case of a 69-year-old woman with a chronic nail lesion that was initially misdiagnosed as onychomycosis and treated with partial onychectomy without histological evaluation. The lesion persisted, and subsequent dermatological evaluation revealed an ulcerated exophytic mass, which was confirmed as an acral nodular melanoma with a Breslow thickness of 7.5 mm. Despite surgical amputation, the patient’s management was complicated by wound infection and limited therapeutic options due to comorbidities. This case highlights the diagnostic challenges of AM and emphasizes the importance of early histopathological assessment and multidisciplinary collaboration for timely intervention and improved outcomes.